Regulation 2017/745 on medical devices, two major innovations: 1) the physiological action of devices consisting of natural materials such as vegetal matrices; 2) the chemical-physical-mechanical action of devices made of "substances", which as such are artificial derivatives - Marcella Marletta; Marcella Marletta (Frontiers Media S.A., 2024)
The Medical Device Regulation 2017/745 (MDR) enables the development of a wide range of innovative products. With respect to Directive 93/42, the MDR explicitly identifies the so-called "medical devices made of substances" (MDMS) through specific requirements. In addition, the MDR expands the definition of medical device (MD) by including the "modification of a physiological or pathological state" as a medical purpose specific to devices. This clarifies that materials interacting with the human body in such a way as to modify its "state" are medical devices. Natural materials, such as vegetal matrices, are characterized by the presence of both functional and structural interactions between their components; they can thus be described as "network/s" and interact with the human body in a coordinated, complex way. Since the "state" of the human body is a network of biological functions, the "network/s over a network" interaction between the natural material and the human body is likely to modify the "state" of the human body. Thus, therapeutic products consisting of natural materials, such as vegetal matrices, seem to fit perfectly into the definition of a medical device. Here we analyze the main characteristics of medicinal products, of medical devices made of substances and of medical devices consisting of natural materials. We see that medicinal products and medical devices made of substances have the common characteristic of being based on substances, either synthetic or derivatives of natural materials, but differ in their mechanism of action. On the other hand, medical devices constituted of natural materials relate to the general category of medical devices and cannot be characterized by any single component, identified as an active component. We also discuss how these characteristics relate to the mechanism of action of each type of product. This analysis should allow to identify the most appropriate path for each product, a necessary step to promote research and development of innovative therapies for a large number of unmet medical needs.